CatLet© Score for Estimation of Benefits of Percutaneous Coronary Intervention Versus Optimal Medical Therapy in Patients with Acute Myocardial Infarction - Xu, Xin; He, Yang; He, Yong-Ming (Cardiology and Cardiovascular Medicine, 2025)
Background: The recently developed Coronary Artery Tree description and Lesion EvaluaTion (CatLet©) angiographic scoring system has adequately accounted for the variability in coronary anatomy and considered both the severity of a coronary artery stenosis and its subtended myocardial territory. This study aims to investigate its potential roles played in guiding treatment strategies. Methods: A total of 544 consecutive acute myocardial infarction (AMI) patients with single vessel disease were retrospectively enrolled and their CatLet scores were calculated. The patients were divided into two groups: high (≥10) versus low (<10) CatLet score group (n=367 versus n=177). The primary endpoint was all-cause death at four-year follow-up. Cox regression survival analysis was performed to determine the benefits of percutaneous coronary intervention (PCI) versus optimal medical therapy in each group. Results: A total of 41 deaths occurred during the follow-up, accounting for 7.7%. The survival rate of all-cause death in the low CatLet score group was similar regardless of whether PCI was performed (P=0.86). However, in the high CatLet score group, the survival rate was significantly higher when PCI was performed as compared to those whose PCI was not performed (P = 0.0067). The multivariable-adjusted hazard ratios (95% CI, P) were 0.20 (0.07-0.62, P=0.005) for PCI in higher CatLet score group and 6.96 (0.22- 205.65, P=0.277) in lower CatLet score group. Conclusions: The CatLet angiographic scoring system, capable to semi-quantify the myocardial territory, can be a useful tool to guide the treatment strategy for patients with AMI. Those with a CatLet score≥10 or more than five myocardial segments involved (CatLet score divided by the coefficient of 2) would benefit from the PCI strategy (http://www.chictr.org.cn; Registry Number: ChiCTR2000033730).